2014
DOI: 10.2337/db13-1715
|View full text |Cite
|
Sign up to set email alerts
|

PTEN Deletion in Pancreatic α-Cells Protects Against High-Fat Diet–Induced Hyperglucagonemia and Insulin Resistance

Abstract: An aberrant increase in circulating catabolic hormone glucagon contributes to type 2 diabetes pathogenesis. However, mechanisms regulating glucagon secretion and α-cell mass are not well understood. In this study, we aimed to demonstrate that phosphatidylinositol 3-kinase (PI3K) signaling is an important regulator of α-cell function. Mice with deletion of PTEN, a negative regulator of this pathway, in α-cells show reduced circulating glucagon levels and attenuated l-arginine–stimulated glucagon secretion both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 39 publications
0
20
0
1
Order By: Relevance
“…There is evidence showing that PTEN modulates hyperglycemia and insulin resistance [54]. In addition, PTEN deletion in pancreatic α-cells protects against HFD-induced insulin resistance [55]. PTEN, through its lipid phosphatase activity, catalyzes the conversion of PIP3 (Akt substrate) to PIP2 by dephosphorylating the 3-position of the inositol ring of PIP3, attenuating Akt/eNOS/NO signaling [56].…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence showing that PTEN modulates hyperglycemia and insulin resistance [54]. In addition, PTEN deletion in pancreatic α-cells protects against HFD-induced insulin resistance [55]. PTEN, through its lipid phosphatase activity, catalyzes the conversion of PIP3 (Akt substrate) to PIP2 by dephosphorylating the 3-position of the inositol ring of PIP3, attenuating Akt/eNOS/NO signaling [56].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, phosphatase and tensin homolog deleted on chromosome 10 (PTEN) antagonizes PI3K actions to negatively regulate the phosphorylation of AKT. Numerous studies revealed that overexpression of PTEN could suppress insulin-induced PtdIns (3,4) P2/PtdIns (3,4,5) P3 PIP3 production, thereby inhibiting AKT activation, GLUT4 translocation and glucose uptake121314.…”
mentioning
confidence: 99%
“…In addition, PTEN deletion in Rip-Cre neurons protected against type 2 diabetes and insulin resistance [32]. Moreover, PTEN deletion in pancreatic a-cells reversed HFD-induced hyperglucagonemia and insulin resistance [33]. Taken together, PTEN might play an important role in the development of insulin resistance and type 2 diabetes.…”
Section: Discussionmentioning
confidence: 93%